132k views
24 votes
Find f(g(3)) given:
*
f (x) = 2x2 – 1
g(x) = 3x
h(x) =
j(x) = x - 5

1 Answer

3 votes

Answer:

161

Explanation:

Given the functions

f (x) = 2x^2 – 1

g(x) = 3x

we are to find f(g(3))

First look for the composite function f(g(x))

f(g(x)) = f(3x)

f(3x) = 2(3x)² - 1

f(3x) = 2*9x² - 1

f(3x) = 18x² - 1

f(g(x)) = 18x² - 1

Substitute x = 3 into the result

f(g(3)) = 18(3)² - 1

f(g(3)) = 18*9- 1

f(g(3)) = 162-1

f(g(3)) = 161

Hence f(g(3)) is 161

User Ivan Danilov
by
4.3k points